Methane concentrations (uncorrected for sediment porosity and Bunsen coefficient) in headspace gas prepared from gravity core GeoB22618-1 recovered from the Danube Deep-Sea Fan - Pape, Thomas; Malnati, Janice; Bohrmann, Gerhard (PANGAEA, 2020)
Gravity cores were collected during cruise M142 in 2017 from several sites at the Danube Deep-Sea Fan, western Black Sea. In order to determine distributions of light hydrocarbons and characterize biogeochemical zonations in the shallow sediments, sediment samples were taken from gravity cores with cut-off syringes and transferred into glass vials to generate a headspace gas volume. The headspace gas samples were analyzed for their concentrations of methane and other light hydrocarbons by use of a gas chromatograph equipped with a capillary column and a flame ionization detector.
Keywords: Black Sea; Danube deep sea fan; gas hydrate; light hydrocarbons; M142; MeBo200; Methane; RV Meteor; SUGAR project